PEMANFAATAN TEKNOLOGI GUNA MEMPERCEPAT PEMBANGUNAN DESA DAN MENINGKATKAN PELAYANAN - Siti Nurul Jannah; Riekya Oktaviani; Abdul Qodir; Muhammad Hilqiya (JOURNAL SAINS STUDENT RESEARCH, 2024)
The purpose of this study is to better understand how technology may promote the quick growth of villages and raise the standard of public services.. Using a qualitative approach and literature methods, this study analyzes various sources of literature, ranging from books, and journals, to articles in magazines, to understand how ICT, or information and communication technology, contributes to increasing the effectiveness of services and development at the village level. The study results show that implementing ICT in villages has had a significant impact. The use of village management information systems (SIMDes) and digital agricultural applications. The community can now easily access information related to the village budget, development programs, and various other public services. This certainly encourages community participation in the development process and increases the accountability of the local administration. The use of ICT not only improves transparency but also speeds up the village's public service delivery process. People no longer have to visit the village office in person to handle a variety of administrative tasks thanks to the online system. Naturally, the community benefits greatly from this quicker and simpler servicing procedure, particularly those who reside in rural regions. Another benefit of using ICT is that it can improve communal wellbeing villages. Digital agriculture applications, for example, can help farmers access market information, predict the weather, and obtain recommendations related to the right cultivation techniques. This can ultimately increase agricultural productivity and farmers' incomeAlthough it has brought many benefits, the use of ICT in villages still faces several obstacles. Limited technological infrastructure, such as uneven internet networks and limited access to computer devices or smartphones, is one of the main challenges. In addition, the low digital literacy among rural communities is also an obstacle in adopting new technologies. To overcome these obstacles, several efforts are needed, such as increasing access to technological infrastructure in villages, especially in remote areas. The government, along with the private sector, can work together to build a better internet network and provide public facilities equipped with computers and free internet access. Then Village communities need to become more digitally literate. Instruction and socialization programs regarding the use of ICT need to be carried out intensively. Village governments, educational institutions, and civil society organizations can actively organize these activities.